Criminal Liability of the Organiser of the Free Nutritious Meals Programme From the Perspective of Criminal Law and Consumer Protection - Moh Kamaluddin; Lily Solichul Mukminah; Novellita Sicillia Anggraini (IHSA Institute, 2026)
The Free Nutritious Meals Programme is a high-risk public food service that requires strict safety and supervision standards, thus necessitating the establishment of a coherent criminal accountability framework. This study employs a normative legal method with a statutory, conceptual, and case approach to examine the relationship between the criminal law regime, consumer protection, and food policy in the implementation of the programme. The results show that beneficiaries fall into the category of functional consumers who are entitled to food safety and service quality. Criminal liability cannot be limited to individual perpetrators but must be built through a layered accountability model involving the central government as the standard setter, local governments as operational implementers, and contractors and vendors as food producers and distributors. The risks of poisoning, adulteration, and supervisory failure underscore the relevance of strict product liability for producers and oversight liability for public officials. This study concludes that an integrative model combining criminal law, consumer protection, and due diligence parameters is the most effective framework for ensuring food safety and accountability in the implementation of the Free Nutritious Meals Programme